Perbedaan kemampuan berpikir kritis dan hasil belajar kognitif dengan model pembelajaran problem based learning berbantuan media audio visual - Meti Herlina; Jayanti Syahfitri; Ilista (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
Utilization of problem based learning models assisted by learning media to improve critical thinking skills and cognitive learning outcomes of students have not run optimally. This study aims to determine the differences in critical thinking skills and cognitive learning outcomes of students with problem based learning (pbl) learning models assisted by audio-visual media in SMA Negeri 06 Bengkulu City. The research method used was quasi experimental with a randomized pretest posttest control group design. The study population was a class XI student of SMAN 06 Bengkulu City with two groups namely experimental and control samples with each 36 people. The instrument used, namely essay question test totaling 5 questions that measure critical thinking and multiple-choice questions totaling 10 questions to measure cognitive learning outcomes. The research data analysis technique used a t-test. The results showed that there were differences in critical thinking skills and student cognitive learning outcomes. This is evident from the t count value of critical thinking skills of 6.414 (> t-table) and cognitive learning outcomes of 5.826 (> t-table). This research concludes that there are differences in critical thinking skills and cognitive learning outcomes of students with PBL models assisted by audio-visual media.